The use of electrostimulation exercise in competitive sport - Maffiuletti, N. A. (International Journal of Sports Physiology and Performance, 2006)
After a brief introduction on electrostimulation methodology and applications in competitive sport for performance optimization, this technical report presents the principal effects of electrostimulation-induced resistance exercise on neuromuscular features. The advantages and limitations of this technique compared with those of voluntary exercise training are also discussed.